THE EFFECT OF MIX BACILLUS SUBTILIS STRAIN BR2CL AND BACILLUS SP. STRAIN BT3CL PROBIOTICS ON COMMERCIAL CARCASS PIECES OF BALI DUCKS FED RATIONS CORTAINING GREEN BEAN SPROUT PEELS FLOUR - K., Milasari; Siti, N. W.; Puspani, E. (Jurnal Peternakan Tropika; Vol 8 No 3 (2020): Vol. 8 No. 3 Tahun 2020; September - December, 2020)
The effect of probiotics mix of Bacillus subtilis strain BR 2 CL and Bacillus sp . strain BT 3 CL through drinking water to a piece of bali duck commercial carcass with feed ingredient is flour of green bean sprout peels . The research was held for two mounth at Farm Fakultas Peternakan, Universitas Udayana at Sesetan farm located on Jalan Raya Sesetan, Gang Markisa number 5, Kelurahan Sesetan, Kecamatan Denpasar Selatan, Kota Denpasar. The design was used a completely random design (CRD) consisting of three treatment and five tests.  The treatment was given for the ducks without being given probiotics through drinking water (A),  the ducks feed with a mix of Bacillus subtilis strain BR 2 CL and Bacillus sp. BT 3 CL through drinking water as much as 2,5 ml (B), ducks were given probiotic mix of Bacillus subtilis strain BR 2 CL and Bacillus sp. BT 3 CL through drinking water as much as 5ml (C).  The observe of variables were included weight and percentage of commercial carcass pieces of upper thighs, lower thighs, wings, chest and back. The results showed that added a probiotics mix Bacillus subtilis strain BR 2 CL and Bacillus sp. BT 3 CL   given rations containing mung bean flour sprouts can produce weight and percentage of carcasses of the upper thighs, lower thighs, wings, breast and back of Bali ducks by giving 2.5ml-5ml not significantly different (P> 0.05). Based on research results can be concluded that adding a probiotics mix Bacillus subtilis strain BR 2 CL and Bacillussp . strain BT 3 C L haven’t effect on weight and percentage of commercial carcass pieces of upper thighs, lower thighs, wings, breasts and backs of Bali ducks.   Keywords : Commercial carcass piece, probiotic, duck